PENEGAKAN HUKUM TERHADAP PENGOPERASIAN PEMBANGKIT TENAGA LISTRIK YANG TIDAK BERIZIN MILIK PERUSAHAAN KELAPA SAWIT - Muhammad Zainal; Ardiansah; Robert Libra (The Juris, 2025)
Law enforcement against the operation of unlicensed power plants owned by palm oil companies in Siak Regency is urgently needed. This research is expected to contribute to the development of legal science, particularly administrative law and energy law, as well as provide practical input for policymakers in realizing better, more equitable, and sustainable electricity governance. The purpose of this research is to analyze law enforcement, obstacles, and efforts to overcome these obstacles against the operation of unlicensed power plants owned by palm oil companies in Siak Regency based on Law Number 30 of 2009 concerning Electricity. The method used is sociological legal research. Based on the research results, it is known that despite clear regulations in Law Number 30 of 2009 concerning Electricity, its implementation still faces obstacles. Several companies still operate power plants without official permits, and law enforcement actions tend to be reactive, with sanctions inconsistent. This demonstrates the need for cross-agency coordination and strengthened oversight mechanisms to ensure more effective law enforcement and a deterrent effect. Obstacles include limited resources, suboptimal coordination, and resistance from some companies, which have made the implementation of Law Number 30 of 2009 less effective. This indicates the need for a more integrated law enforcement strategy, increased oversight capacity, and community empowerment to create a deterrent effect for violators. Efforts to overcome these obstacles include inter-agency coordination, increased oversight capacity, simplified licensing procedures, and community participation, all complementary measures. A more structured coordination mechanism is recommended between the Environmental Agency, the Ministry of Public Works and Housing (DPMPTSP), law enforcement officials, and other relevant agencies. This will expedite prosecution of companies operating unlicensed power plants and avoid overlapping authority.